2016
DOI: 10.5433/1679-0359.2016v37n6p3983
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance of sugarcane cultivated under quantities of sugarcane straw on the soil surface

Abstract: Mechanized harvesting has become increasingly common in the sugarcane production system. The sugarcane straw removed by mechanical harvesting could be converted into ethanol or be used to generate electricity by burning the material. At the same time, it is important to determine the amount of biomass that could be removed from the soil surface without damage to the cane crop. The agronomic performance of sugarcane was evaluated by growing the variety RB92579 under different amounts of sugarcane straw on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…In the past few years, the straw removal effects on sugarcane yield have been investigated in different locations in south-central Brazil [5,12,14,15]. However, there is no consensus about the sugarcane yield responses to straw removal.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, the straw removal effects on sugarcane yield have been investigated in different locations in south-central Brazil [5,12,14,15]. However, there is no consensus about the sugarcane yield responses to straw removal.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with recent studies also conducted in central-southern Brazil . Oliveira et al (2016) The effect of straw removal on stalk yield was similar at both mills. Nevertheless, at the Univalem mill the highest stalk yield was obtained under smaller amounts of straw compared to the straw amount that induced the highest yields at the Bom Retiro mill.…”
Section: Sugarcane Straw Removal Vs Stalk Yieldmentioning
confidence: 83%
“…According to , the maintenance of 10 Mg ha -1 of sugarcane straw was enough to sustain plant growth and yield in an Oxisol. In the same soil type, Oliveira et al (2016) observed the highest stalk yields under 9.6 and 4.7 Mg ha -1 of straw retained for the cane-plant and first ratoon cycles, respectively. Variation in the minimum amount of sugarcane straw needed to sustain soil and plant yields likely depends on soil type, crop management, topography and climate conditions Seebaluck and Leal, 2015;Carvalho et al, 2016;.…”
Section: Introductionmentioning
confidence: 78%
“…found that 4-9 Mg ha -1 of straw left on the soil is adequate to maintain the crop productivity. Oliveira et al (2016) verified that to increase cane yield it is necessary to maintain 9.5 Mg ha -1 and 4.7 Mg ha -1 of straw in the first (1st ratoon)…”
Section: Changes On Sugarcane Biomass and Its Relationship With Soil ...mentioning
confidence: 93%